A Need Analysis on English for Civic Education from the Students’ Perspectives - Eka Fajar Rahmani (PT Mattawang Mediatama Solution, 2023)
This study aims at analyzing the needs of students of Civic Education study program towards English. It is conducted to provide a basis for ESP lecturers or practitioners in developing handout or teaching learning materials and activities which are suitable for the Civic Education study program students This is a descriptive study. the participants were 39 first-semester students of Civic Education study program. The tool of data collection was questionnaire consisting of 7 items asking about the students’ needs. The data were analyzed using percentages, and presented in charts. Most students (79.5%) said English is important, indicating they require it. They lack English knowledge (79.5%) and consider their English skills moderate (63.2%). Their English abilities, activities, exercises, and subject subjects focused on speaking (79.5%) and group work (74.4%), with citizenship and human rights (66.7%) being the most requested topic. This study investigates Civic Education students'' language learning demands and English’s impact on academic and career success. Most pupils regarded English’s global importance and academic and professional potential. The survey concluded that Civic Education students need linguistic support and courses because they are lack of knowledge of English terms. Different self-assessed English levels require different instructional techniques and language support to master.